Network Ethics: Information and Business Ethics in a Networked Society - Floridi, Luciano (Journal of business ethics, 2009)
This article brings together two research fields in applied ethics – namely, information ethics and business ethics– which deal with the ethical impact of information and communication technologies but that, so far, have remained largely independent. Its goal is to articulate and defend an informational approach to the conceptual foundation of business ethics, by using ideas and methods developed in information ethics, in view of the convergence of the two fields in an increasingly networked society.